Parental Communication in Supervising and Preventing the Negative Impact of Gadgets on Children During Covid-19 in Kisaran Timur District, Asahan Regency - Annisa Nur Rahmah; Lusiana Andriani Lubis; Rahmanita Ginting (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
This study aims to analyze the communication between parents and children in monitoring children against the negative effects of gadgets during the covid-19 pandemic in Kisaran Timur District, Asahan Regency. The total populations are 6,818 people, with a sample of 99 people taken by rational sampling from 12 sub-districts Kisaran Timur District. This study employs correlational research with data collection techniques using questionnaires and spearman's data analysis. This study finds that communication between parents and children in monitoring the use of gadgets has a significant effect. Supervision is carried out by providing a good understanding of using gadgets, monitoring, and also implementing rules for using gadgets. Furthermore, communication between parents and children in preventing the negative effect of gadgets during covid-19 pandemic has a high affecting value. Prevention is carried out by reducing the opportunities to use gadgets for children, limiting the use of gadgets, setting duration, and also discussing to build parental trust in children. Communication between parents and children affects the monitoring and preventing the negative effects of gadgets.